It doesn't matter what they say, it matters how they behave: Parental influences and changes in body mass among overweight and obese adolescents. (1st January 2016) - Zarychta, Karolina; Mullan, Barbara; Luszczynska, Aleksandra
Abstract: Objective: This study investigated whether the relationships between perceived parental behaviors (dietary behaviors, physical activity, and verbal pressure) and changes in adolescents' body mass index (BMI) were mediated by adolescents' physical activity and dietary behaviors. The associations were tested among overweight and obese adolescents. Design: Longitudinal data were collected three times, with a 2-month interval between Time 1 (T1) and Time 2 (T2), and a 13-month interval between T2 and Time 3 (T3) in the group of adolescents ( N  = 100) aged 13–19. There was no experimental manipulation. Mediation analyses with two sequential mediators were conducted. Main measures: Participants completed the questionnaires assessing their dietary behaviors, physical activity (mediators), perceived parental behaviors, and verbal pressure (independent variables). Adolescents' weight and height were measured objectively (with BMI constituting the outcome variable). Results: Adolescents who perceived that their parents engaged in a healthy diet and frequent physical activity (T1) self-reported a healthier diet (T2 and T3), higher levels of physical activity (T2 and T3), and their combined index of healthy lifestyle was higher (T2 and T3). In turn, adolescents' behaviors (T2 and T3) were related to lower BMI (T3). Perceived behaviors of parents had a significant, indirect effect on a BMI reduction. There were no effects of the perceived parental verbal pressure (T1) through adolescents' behaviors (T2) on adolescents' BMI (T3). Conclusion: Perceived parental modeling of healthy diet and frequent physical activity, but not verbal pressure, predicted adolescents' behaviors (diet, physical activity, and a combined lifestyle index) and, in turn, a reduction in their BMI. The role of parents' health behaviors (diet and physical activity) should be taken into account when considering adolescents' overweight and obesity prevention and treatment programs. Highlights: We investigated predictors of nutrition behavior, physical activity and BMI reduction. Adolescents with overweight and obesity were followed up for 13 months. Perceived parental modeling predicted adolescents' behaviors and BMI reduction. Perceived parental verbal pressure had no effect on adolescents' behaviors and BMI.